PENGARUH FINANCIAL LITERACY DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR DENGAN LOCUS OF CONTROL SEBAGAI VARIABEL MEDIASI Pada Generasi Z di Kota Batang - Sekar Intan Guphita; C. Tri Widiastuti; Rita Meiriyanti (Jurnal Ilmiah Manajemen dan Akuntansi, 2026)
This study to examine and analyze the influence of Financial literacy and financial attidudes on Financial Management Behavior, with Locus of Control as a mediating variable among Generation Z in Batang City. This research is quantitative. The population in this study was gwnwration Z in Batang City, with a sample size of 100 respondents. Data collection was conducted by distributing an online questionnaire via Goggle Form. Data analysis techniques in this study used structural model analysis (Inner Model), measurement model analysisis (Outer Model), and hypothesis testing. Data processing was performed using SmartPLS 4 sofware. The result showed that Financial literacy had no significant effect on Financial Management Behavior, while Financial Attitude had a significant effect on Financial Management Behavior. Financial literacy significantly affected Locus of Control, Financial Attitude significantly affected Locus of Control, and Locus of Control did not significantly affect Financial Management Behavior. Locus of Control was unable to mediate the influence of Financial literacy and financial attitudes on Financial Management Behavior.